(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Object Oriented Analysis is concerned with specifying system requirements and analyzing the application domain. Object Oriented Design is concerned with implementing the requirements identified during OOA in the application domain. In this paper, the brief overview of object oriented concepts, its analysis and designing concepts, their strategies with its various advantages and disadvantages have been discussed.